1999
DOI: 10.1046/j.1423-0410.1999.7720088.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Time‐Resolved Fluoroimmunoassay for the Analysis of Normal Prion Protein in Human Blood and Its Components

Abstract: The majority of blood PrP(c) is found in the platelet and plasma compartments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
101
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(111 citation statements)
references
References 34 publications
9
101
0
1
Order By: Relevance
“…Interestingly, this processed soluble form of PrP that starts at Gly 90 showed an electrophoretic mobility on SDS-PAGE similar to PrP [27][28][29][30] , the protease-resistant core of PrP Sc (15). Using a time-resolved fluoroimmunoassay, MacGregor et al (22) showed that soluble forms of PrP are present in various human blood fractions. It is still unclear whether soluble PrP can be converted into PrP Sc .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, this processed soluble form of PrP that starts at Gly 90 showed an electrophoretic mobility on SDS-PAGE similar to PrP [27][28][29][30] , the protease-resistant core of PrP Sc (15). Using a time-resolved fluoroimmunoassay, MacGregor et al (22) showed that soluble forms of PrP are present in various human blood fractions. It is still unclear whether soluble PrP can be converted into PrP Sc .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there is evidence for a soluble form of PrP C in the medium of cultured cells (9 -13), in human cerebrospinal fluid (14), in human blood (22), and released from activated human platelets (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the direct detection of conformational changes of the prion protein can be excluded: firstly, the amide I and amide II regions were intentionally excluded from the analysis of the differentiation between BSE-positive and BSE-negative such that the observed discrimination potential is unlikely to be based on specific protein signatures. Secondly, the concentration of prion proteins in serum [22][23][24] is less than 50 ng ml 21 and, hence, well below the mid-infrared detection limit. In summary, we have shown that the automation of the DPR process was successfully implemented into a DPR research system resulting in added convenience, simplified sample and data logistics and an improvement in reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the pathological diagnosis of TSE is currently made principally on the basis of postmortem preparations of CNS tissues, highlighting the need for the development of a more rapid diagnostic method using body fluids, especially blood (6,27). For this purpose, several methods have been proposed and examined for prophylactic use (23,30,32). However, none of these methods has proved to be sufficient for the purposes (5,7,20,29).…”
mentioning
confidence: 99%